324. COVID-19-Associated Pulmonary Aspergillosis (CAPA) at Veterans Affairs (VA) Hospitals in Southern California and Arizona. (4th December 2021) - Fang, Michelle; Nguyen, Phuong Khanh; Chau, Tony T; Doan, Ashley; Varker, Andrew S; Renna, Marshall T; Nakamatsu, Raul; Graber, Christopher J; Goetz, Matthew B; Goetz, Matthew B; Hoenigl, Martin; Hoenigl, Martin; et al.
Abstract: Background: The data on CAPA in the U.S. are limited to date and clinical characteristics unique to this phenomenon have not been widely reported. Methods: This retrospective observational study was conducted at multiple VA hospitals across southern California and Arizona. CAPA cases were identified in inpatients with laboratory-confirmed COVID-19 based on microbiologic or serologic evidence of aspergillosis and pulmonary abnormalities on imaging, and were classified according to ECMM/ISHAM consensus definitions. Characteristics of interest included immunosuppressive/modulatory agents used prior to onset of CAPA, COVID-19 disease course, length of hospitalization, and mortality. Results: Seventeen patients with probable (18%) or possible (82%) CAPA were identified from April 2020 to March 2021. Values below reported as medians. All patients were male and 13 (76%) were white, with age 74 years and BMI 26 kg/m 2 . Baseline comorbidities included diabetes mellitus (47%), cardiovascular disease (65%), and pulmonary disease (71%). Evidence of aspergillosis was mostly based on respiratory culture, with mainly A. fumigatus (75%). Systemic corticosteroids were used in 14 patients, with a total dose of 400 mg prednisone equivalents starting 10 days prior to Aspergillus detection. Patients also received tocilizumab (18%), leflunomide (6%), tacrolimus (6%), mycophenolate (6%), and investigational agent LSALT or placebo (6%); 2 patients (12%) did not receive any immunosuppression/modulation. Length of hospitalization for COVID-19 was 22 days. Death occurred in 12 patients (71%), including all patients with probable CAPA, at 34 days after COVID-19 diagnosis and 16 days after CAPA diagnosis. Eight patients (47%) were treated for aspergillosis; mortality did not appear to differ with treatment (75% vs. 67%). Table 1. COVID-19 Inpatient Characteristics Table 2. Incidence of Aspergillus Growth on Respiratory Culture Conclusion: This case series reports high mortality among patients with CAPA; the primary contributor to this outcome is unclear. Frequency of lower respiratory tract sampling in patients with COVID-19 may have limited diagnosis of CAPA. Interestingly, inpatient respiratory cultures with Aspergillus spp. increased compared to previous years. Future work will attempt to identify risk factors for CAPA and attributable mortality via comparison to inpatients with COVID-19 without CAPA. Disclosures: Matthew B. Goetz, MD, Nothing to disclose Martin Hoenigl, MD, Astellas (Grant/Research Support)Gilead (Grant/Research Support)Pfizer (Grant/Research Support) Martin Hoenigl, MD, Astellas (Individual(s) Involved: Self): Grant/Research Support; F2G (Individual(s) Involved: Self): Grant/Research Support; Gilead (Individual(s) Involved: Self): Grant/Research Support; Pfiyer (Individual(s) Involved: Self): Grant/Research Support; Scýnexis (Individual(s) Involved: Self): Grant/Research Support Sanjay Mehta, MD, D(ABMM), DTM&H, MedialEarlySign (Consultant)ZibdyHealth (Employee, Medical Officer - Unpaid)